Perlindungan Hukum Konsumen dalam Pembelian Merchandise K-Pop Melalui Sistem Pre-Order pada Group Order (GO) di Indonesia - Ni Ketut Putri Ratih Suwandewi (International Forum of Researchers and Lecturers, 2026)
The growth of e-commerce has spurred the emergence of various transaction models, one of which is the Group Order (GO) utilizing a pre-order system a method widely used for purchasing K-Pop merchandise. While this mechanism offers consumers a convenient way to acquire official merchandise, it also entails risks such as delivery delays and discrepancies regarding the goods received. These circumstances highlight the importance of legal protection for consumers involved in GO transactions. This study aims to analyze the legal relationship between consumers and GO organizers and to examine the forms of legal protection available to consumers purchasing K-Pop merchandise through GO pre-order systems. Employing a normative legal research method, the study utilizes both statutory and conceptual approaches, with data analyzed through descriptive-analytical methods based on a literature review. The findings indicate that the legal relationship between the consumer and the GO organizer arises from an agreement that meets the legal requirements for a valid contract, thereby establishing rights and obligations for both parties. Although the practice of purchasing merchandise via GO pre-order systems is not explicitly regulated by Indonesian legislation, consumers remain entitled to legal protection under the provisions of the Indonesian Civil Code (KUHPer) and Law Number 8 of 1999 concerning Consumer Protection; thus, they possess a legal basis to demand the fulfillment of their rights and seek redress for any losses incurred.